Associations between perceptions of care and women's childbirth experience: a population-based cross-sectional study in Rwanda - Judith U. Mukamurigo; Marie Berg; Joseph Ntaganira; Laetitia Nyirazinyoye; Anna Dencker (BMC, 2017)
Abstract Background In recent years Rwanda has achieved remarkable improvement in quality of maternity care services but there is evidence of deficiencies in care quality in terms of disrespectful care. Women's overall childbirth experience is an important outcome of childbirth and a factor in assessing quality of care. The aim of this study was to investigate how women's overall childbirth experience in Rwanda was related to their perceptions of childbirth care. Methods A cross-sectional household study of women who had given birth 1-13 months earlier (n = 921) was performed in the Northern Province and in the capital city. Data was collected via structured interviews following a questionnaire. Significant variables measuring perceptions of care were included in a stepwise forward selection logistic regression model with overall childbirth experience as a dichotomised target variable to find independent predictors of a good childbirth experience. Results The majority of women (77.5%) reported a good overall childbirth experience. In a logistic regression model five factors of perceived care were significant independent predictors of a good experience: confidence in staff (Adjusted OR 1.73, 95% CI 1.20-2.49), receiving enough information (AOR 1.44, 95% CI 1.03-2.00), being treated with respect (AOR 1.69, 95% CI 1.18-2.43), getting support from staff (AOR 1.75, 95% CI 1.20-2.56), and having the baby skin-to-skin after birth (AOR 2.21, 95% CI 1.52-3.19). Conclusions To further improve childbirth care in Rwanda and care for women according to their preferences, it is important to make sure that the childbirth care includes the following quality aspects in national and clinical guidelines: build confidence, provide good information, treat women and families with respect, provide good professional support during childbirth and put the newborn baby skin-to-skin with its mother early after birth.